Antidiabetic and Antiinflammatory Studies of Alpinia galanga Rhizome - B. Jaju, Shivkanya; Indurwade, N.H.; Sakarkar, D.M.; Ali, M.; Fuloria, N.K. (Asian Journal of Chemistry, 2010)
Alpinia galanga rhizome is widely used in traditional medicine to treat various human aliments. In order to prove scientifically the ethnomedical uses of Alpinia galanga, the antiinflammatory and antidiabetic properties of the methanolic extract and isolated galangoisoflavonoid (AG12) component of Alpinia galanga in experimental animal models are investigated. The obtained results were found to be significant.